2022
DOI: 10.3390/cells11030513
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Telomere Length Correlates with Extended Female Fertility

Abstract: Current social trends of delayed reproduction to the fourth and fifth decade of life call for a better understanding of reproductive aging. Demographic studies correlated late reproduction with general health and longevity. Telomeres, the protective ends of eukaryotic chromosomes, were implicated in various aging-associated pathologies and longevity. To examine whether telomeres are also associated with reproductive aging, we measured by Southern analysis the terminal restriction fragments (TRF) in leukocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Telomere length is known to directly correlated with both life expectancy and reproductive life span [ 77 ], [ 78 ], [ 79 ]. Comparison of telomere lengths in the leukocytes of women revealed that the average telomere length in the extended fertility group is significantly longer than in the normal fertility group [ 80 , 81 ]. Telomeres are shorter in the leukocytes of postmenopausal women than those of a similar age but still menstruating [ 82 ].…”
Section: Main Mechanisms Of Ovarian Agingmentioning
confidence: 99%
“…Telomere length is known to directly correlated with both life expectancy and reproductive life span [ 77 ], [ 78 ], [ 79 ]. Comparison of telomere lengths in the leukocytes of women revealed that the average telomere length in the extended fertility group is significantly longer than in the normal fertility group [ 80 , 81 ]. Telomeres are shorter in the leukocytes of postmenopausal women than those of a similar age but still menstruating [ 82 ].…”
Section: Main Mechanisms Of Ovarian Agingmentioning
confidence: 99%
“…In 2014, a new software named TeloTool (version 1.3.0.0) was developed, which fits the telomeric signal with a Gaussian function, making it particularly useful for samples with a unimodal distribution of the telomere-specific signal [20]. Over the years, TeloTool has been successfully used to examine the telomere length's association with reproductive aging [21] and to evaluate telomere elongation processes specific to the alternative lengthening of telomeres (ALT) mechanism, which elongates telomeres in up to 15% of human cancers [22].…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, a new so named TeloTool (version 1.3.0.0) was developed, which fits the telomeric signal Gaussian function, making it particularly useful for samples with a unimodal distr of the telomere-specific signal [20]. Over the years, TeloTool has been successfully u examine the telomere length's association with reproductive aging [21] and to ev telomere elongation processes specific to the alternative lengthening of telomeres mechanism, which elongates telomeres in up to 15% of human cancers [22]. [19,20,23] was obtained from the Google Scholar database (accessed on 29 August 2023), and each of the papers was manually verified for the use of the corresponding method in calculating telomere length from TRF blots.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, women's ovarian reserve 15 , 16 and anti-müllerian hormone (AMH) levels, 15 a marker of ovarian reserve, decline steadily with age, increasing the risk of aging-associated diseases. 3 On the other hand, shorter TL in blood is associated with lower oocyte quality 17 and higher segregation errors 18 and aneuploidy rates. 19–21 …”
Section: Introductionmentioning
confidence: 99%